T-DNA Insertional Mutagenesis for Activation Tagging in Rice - Jeong, Dong-Hoon (American Society of Plant Biologists, 2002)
We have developed a new T-DNA vector, pGA2715, which can be used for promoter trapping and activation tagging of rice (Oryza sativa) genes. The binary vector contains the promoterless β-glucuronidase (GUS) reporter gene next to the right border. In addition, the multimerized transcriptional enhancers from the cauliflower mosaic virus 35S promoter are located next to the left border. A total of 13,450 T-DNA insertional lines have been generated using pGA2715. Histochemical GUS assays have revealed that the GUS-staining frequency from those lines is about twice as high as that from lines transformed with the binary vector pGA2707, which lacks the enhancer element. This result suggests that the enhancer sequence present in the T-DNA improves the GUS-tagging efficiency. Reverse transcriptase-PCR analysis of a subset of randomly selected pGA2715 lines shows that expression of the genes immediately adjacent to the inserted enhancer is increased significantly. Therefore, the large population of T-DNA-tagged lines transformed with pGA2715 could be used to screen for promoter activity using the gus reporter, as well as for creating gain-of-function mutants.